CDK4/6 inhibitors target SMARCA4-determined cyclin D1 deficiency in hypercalcemic small cell carcinoma of the ovary - Yibo Xue (Nature Portfolio, 2019)
Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is driven by SMARCA4 loss. Here the authors demonstrate that SCCOHT cells are highly sensitive to CDK4/6 inhibition and provide mechanistic insights, whereby this druggable vulnerability is driven by cyclin D1 deficiency induced by SMARCA4 loss.